2019
DOI: 10.1111/tri.13431
|View full text |Cite
|
Sign up to set email alerts
|

Effects of immunoadsorption combined with membrane filtration on complement markers – results of a randomized, controlled, crossover study

Abstract: ClinicalTrials.gov number: NCT01698736. SUMMARYThe complement system has been implicated in several kidney diseases, such as antibody-mediated rejection after kidney transplantation. Antibody-depletion techniques allow successful ABO-and/or HLA-incompatible transplantation. Considering the IgG removal, the use of semi-selective immunoadsorption (IA) has been advocated. However, because of results on incomplete IgM depletion, the adjunctive use of membrane filtration (MF) has been proposed to enhance the remova… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…IA could be coupled with membrane filtration (Monet ® ). Monet ® filter was used to enhance the removal of molecules possibly involved in the post-transplantation rejection risk such as IgM, C1q, properdin, mannose-binding lectin [8]. It was associated with IA when HLA antibody titer was high (i.e., >12,000).…”
Section: Statistical Analysesmentioning
confidence: 99%
“…IA could be coupled with membrane filtration (Monet ® ). Monet ® filter was used to enhance the removal of molecules possibly involved in the post-transplantation rejection risk such as IgM, C1q, properdin, mannose-binding lectin [8]. It was associated with IA when HLA antibody titer was high (i.e., >12,000).…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Thus, it was shown that IA combined with MF can remove C1q as well as other complement pathway factors, such as properdin and mannose-binding lectin. 14,15 Recently, we have shown that DFPP significantly removes high-molecular-weight proteins from the hemostatic system and decreases levels of protein S (PS) and tissue factor pathway inhibitor (TFPI). 16 In the present study, the aim was to assess whether IA, with or without MF, alters the loss of high-molecular-weight proteins from the hemostatic system.…”
Section: Introductionmentioning
confidence: 99%
“…Besides IgM and C1q, combined apheresis was also shown to interfere with the lectin and the alternative pathway, as elimination of MBL and properdin was enhanced [16]. This finding might strengthen the effect of MF on IgM elimination since it was shown that IgM can directly bind MBL thereby activating the lectin pathway [28].…”
Section: Discussionmentioning
confidence: 93%
“…We have previously demonstrated in a randomized controlled crossover trial that the combination of nonantigen-specific (i.e., semi-selective) immunoadsorption (IA) together with membrane filtration (MF) allows for efficient elimination of macromolecular effector components such as IgM, C1q, and mannose-binding lectin (MBL) in addition to substantial IgG removal [15,16]. To account for the different pathomechanisms involved in treatment-resistant humoral rejection, we have applied this innovative concept of combined apheresis in a consecutive series of 4 highly sensitized kidney transplant patients with severe early acute C4d+ humoral rejection refractory to standard-of-care treatment with semi-selective IA.…”
Section: Introductionmentioning
confidence: 99%